(3LeY GdahGFO GdefJNHI GdUMjMI ef GdNhGU GdeLQHIs - (3nCoHh GdnYdGA GdEnjGOj , RgQ Hf YHO Gdedc Hf eMeO Hf eQhGf GHf RgQ, CHh GdYdGA,J (B525 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje LeY GdahGFO GdUMjMI GdeLQHI, bO Cdag GdhRjQ GdMcje CHhGdYdGA GHf RgQ (B((3jdi Pdc MQha gi YdGeGJ dCSeGA ef hbY PcQg ai gPG GdcJGH eKGd Pdc (B) (3c dcjeGhS s
(3BNQgG (B:s
(3MQa GdjGA, jHQhM(B: (3gh Tcd Ydi gjFI GdEfSGf jchf ai HdGO GdCJQGc, jchf JMJ GdCQV, hdGjbdYg EdG GdcdH, hQHeG eGJ hbJ bdYg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B279 - (3U(B341s
(3GdfSNI HgG MhGTs
(3GfXQ agQS GdWH HQbe (B78 (3, (B179 s
(3MjK fSHg dCHi GdeYGdi YHOGdedc EHf CHj GdYdGA RgQ GdeJhai SfI (B557(3g`s
(3fSNI NGeSI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdWHs